Analisis Break Even Point Dalam Penentuan Proyeksi Laba Pada Usaha Kedai Mafazah Pagar Dewa Kota Bengkulu - Siti Martini; Suwarni Suwarni; Tito Irwanto (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Micro, Small, and Medium Enterprises (MSMEs) have a very important part and can become the backbone of the economy in Indonesia and also one of the things that should be given great attention. Break Event Point (BEP) is a condition where the amount of income is equal to the amount of costs sacrificed, or a situation where the business does not make a profit and does not suffer a loss. Profit projection is a plan or profit target of an institution over a period of time. The purpose of this study is to determine the implementation of BEP with the data collection method used is documentation, then it used as material for profit projections in the future. The results of the research and discussion show that the Break Even Point analysis can see how many the break-even point of business and increase sales and keeps the books at Kedai Mafazah using BEP analysis and can see future profits assuming BEP analysis in order to increase profits or increase the desired profit. Keywords: Break Even Point, Profit Projection